(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of this study was to provide a detailed computed tomographic (CT) reference of the normal dromedary camel foot. Six hind limbs obtained from three dromedary camel cadavers with no evidence of orthopedic disease of the foot. In all limbs, computed tomography was performed in both soft tissue and bone windows; transverse, sagittal and dorsal planes slice thickness of 1 mm and matrix size of 512x512. In computed tomography images the proximal, middle and distal phalanges, proximal and distal sesamoid bones, superficial and deep digital flexor tendons, collateral ligaments and the inter-digital ligament were clearly identified. The computed tomography images allowed excellent delineation between the cortex and medulla of bones and the trabecular bone was clearly depicted. The transverse images provided good visualization of the different bony and soft tissues and vessels of the camel foot. The sagittal images allowed a detailed evaluation of the contour of the joints while, the dorsal images allowed full assessment of the collateral ligaments of the joints. In this study, computed tomography was a useful imaging tool for identification and characterization of the osseous and soft tissue structures of the dromedary camel foot. This technique may be of value when results from other diagnostic imaging techniques are inconclusive. The images provided will serve as a computed tomography reference for the dromedary camel foot.